2011
DOI: 10.4067/s0718-40262011000500010
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida en pacientes con hiperhidrosis primaria sometidos a simpatectomía videotoracoscópica

Abstract: Quality of life after videothoracic simpathectomy in patients with primary hyperhidrosisIntroduction: Primary hyperhidrosis is characterized by excessive sweating that exceeds the physiological needs to maintain thermal homeostasis of the body. This study aims to assess the change in quality of life of patients operated on videothoracoscopic sympathectomy. Materials and Methods: We included all patients operated with this technique in the period between 2004 and 2010, in FACh Hospital. A standardized cuestiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
0
0
2
Order By: Relevance
“…Regarding the location of the CH, the study by Soto et al aligns with our findings, with the back and abdomen being the most common areas affected [ 11 ]. In Latin America, studies like that of Zamarin et al reported rates as high as 78% in patients, affecting primarily more than one body segment, with the back being the most affected [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the location of the CH, the study by Soto et al aligns with our findings, with the back and abdomen being the most common areas affected [ 11 ]. In Latin America, studies like that of Zamarin et al reported rates as high as 78% in patients, affecting primarily more than one body segment, with the back being the most affected [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Cuba, the study by Soto et al did not report any of these complications [ 11 ], while the study by Zacarías et al recorded complications in 1.1% of patients [ 23 ]. Even in the study by Zamarin et al in Chile, the rate of these complications was 3.2% [ 5 ]. Among these studies, bleeding was the most common complication, whereas, in our registry, there was only one case of hemothorax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En los estudios latinoamericanos, el seguimiento a largo plazo no sobrepasa los ocho años 6,[14][15][16][17][18][19][20] . A nivel global, los estudios con mayor seguimiento son el de Askari, et al 3 , con 51 pacientes evaluados en promedio durante 77 meses (rango 6 a 189 meses), después de la simpatectomía torácica bilateral, y el de Zacherl, et al 10 , con 293 pacientes con seguimiento mayor de 15 años.…”
Section: Discussionunclassified
“…Preocupación de sociedades científicas, congresos mundiales y grandes avances en general, pero algunos aspectos no cuentan con suficiente evidencia 1,2 . La cirugía se presenta como la opción curativa, más allá del sudor compensatorio y otros efectos secundarios potenciales, pero se reportan diferencias tanto anestésicas como quirúrgicas [3][4][5][6] . En relación a tales controversias se generan las siguientes interrogantes que constituyen nuestro problema a investigar: -Qué tipo de anestesia: ¿anestesia general con tubo endotraqueal simple y oxigenación en apnea es efectiva y segura para este procedimiento?…”
Section: Introductionunclassified